Financial Analysis Through The Application of Green Growth Economy (GGE) As A Moderation Variable Affects The Increase In GDP / GNP Economic Income In Indonesia During The Covid-19 Period Towards The New Normal - Margaretha Prihatiningsih; Yusup Hari Subagyo; Vitalis Ari Widyaningsih (Publikasi Indonesia, 2022)
The study aims to determine whether the company's financial performance through financial ratio analysis and the application of GGE (Green Growth Economy) as a moderation variable affects the increase in GDP / GNP economic income during the Covid-19 period towards the New Normal can be achieved properly. The population in the study was 36 Main Board Companies in the Property and Real-Estate Sub-Sector, a sample of 17 companies with a purpose sampling method. Multiple Correlation Regression Analysis Method with t TEST and F TEST and Classical Assumption Test using SEM Analysis Model (Structure Equation Model) & MRA Test (Moderating Regression Analyze). Based on the Results of the Analysis of Mediation Tests With MRA Regression (Moderating Regression Analyze), Cash Ratio, NPM with a significance value of 0.386 & 0.244 greater than 0.05 Then indirectly through GGE is not able to affect GDP / GNP which means it is rejected. Meanwhile, DER and ROA with a significance value of 0.016 & 0.042 are able to affect GDP / GNP. Likewise, DER & ROE with significance values of 0.002 & 0.007 < 0.05 Then indirectly through GGE is able to affect GDP / GNP. CAR, NPM through GGE with significance values of 0.538, 0.171 > 0.05 Then it is not able to affect GDP/GNP which means it is rejected. While DER & ROA through GGE as a moderation variable with a significance value of 0.029 & 0.016 is indirectly able to affect GDP / GNP. DER, ROE, NPM via GGE as moderation variables with a significance value of 0.038; 0,002; 0.046 < 0.05 Then it can affect GDP/GNP. Sedankan Cash, DAR, NPM via GGE as moderation variables with significance values 0.196;0.193; 0.535 > 0.05 Then it is not able to affect GNP/GDP which means it is rejected.